FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT SURYA CAHAYA INTI DENPASAR - I Gusti Gde Oka Pradnyana; Windry Anggraini Kase (Forum Manajemen STIMI Handayani Denpasar, 2014)
The objectives of this research is to determine whether there is influenceof the office layout and the physical work environment on employee performanceand simultaneous partial, as well as to determine which of the two factors which arepredominant affect the performance of employees at PT. Surya Cahaya Inti Denpasar.Factors office layout to note is the shortest distance principle, the principle of a seriesof work, the principles concerning the use of all rooms, the principle of the changein the composition of the workplace, the principle of integration activities, and jobsatisfaction for employees. Factors While the physical work environment is the air,sound, light, color, safety, cleanliness, and space.Through this study the authorspropose the following hypothesis: There is the influence of the office layout and the physical work environment on the performance of employees of PT. Surya Cahaya Inti Denpasar and simultaneous partial. The population in this study were employeesof PT. Surya Cahaya Inti Denpar that about 20 people. Data collection methods usedin this study descriptive correlational, multiple regression analysis techniques werecalculated using SPSS version 13.0 anlisis to facilitate researchers in data processingto be fast and efficient. The results and discussion indicate that the hypothesis ofoffice layout and the physical work environment is partially positive and significantinfluence.From the results of the study also showed that the hypothesis of officelayout and the physical work environment simultaneously positive and significanteffect.While the most dominant factor affecting the performance of employees is thephysical work environment factors.Based on this study suggested to the Chairman ofPT. Surya Cahaya Inti Denpasar to keep attention to the arrangement of the officespace and the physical work environment Company.